2004
DOI: 10.2298/hel0440113d
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of tocopherol mutations in sunflower

Abstract: Two new inbred lines, T589 (medium β-tocopherol content) and T2100 (high γ-tocopherol content), recently developed in CSIC, Cordoba, Spain, have been crossed to known tph1 and tph2 mutations which possessed the same phenotypes and which were obtained at VNIIMK, Krasnodar, Russia. Genetic identification of these recessive mutations with TLC profiles showed the new medium β-tocopherol mutation to be allelic to tph1 and the new high γ-tocopherol mutation to be allelic to tph2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…These results were confirmed in the analysis of F 2 seeds, which also showed high gamma‐tocopherol contents of 960 ± 25 g kg −1 (T2100 × LG‐17), 970 ± 34 g kg −1 (T2100 × IAST‐1), and 980 ± 16 g kg −1 (T2100 × IAST‐540). Demurin et al (2004) evaluated the F 1 from a cross between the line VK 175, a line with tph 2 tph 2 genotype derived from LG‐17, and T2100, concluding that T2100 was allelic to tph 2. The results of the present research suggested that tph 2 alleles are present in the four lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were confirmed in the analysis of F 2 seeds, which also showed high gamma‐tocopherol contents of 960 ± 25 g kg −1 (T2100 × LG‐17), 970 ± 34 g kg −1 (T2100 × IAST‐1), and 980 ± 16 g kg −1 (T2100 × IAST‐540). Demurin et al (2004) evaluated the F 1 from a cross between the line VK 175, a line with tph 2 tph 2 genotype derived from LG‐17, and T2100, concluding that T2100 was allelic to tph 2. The results of the present research suggested that tph 2 alleles are present in the four lines.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes controlling tocopherol biosynthesis have been mapped in sunflower. The Tph1 gene determining increased beta‐tocopherol content in sunflower lines LG‐15 and T589 (Demurin et al, 2004) was mapped to LG 1 of the sunflower genetic map (Vera‐Ruiz et al, 2006). The results of the present research demonstrated that both the Tph1 and the Tph2 genes will segregate independently, since they are located in different linkage groups, and the identification of molecular markers linked to them provides an efficient system to select the tph1tph1tph2tph2 genotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic identification by the allelic test showed the new medium β-tocopherol mutation to be allelic to tph1 and the new high γ-tocopherol mutation to be allelic to tph2 (Demurin et al, 2004;Vera-Ruiz et al, 2005). The δ-tocopherol content in the phenotype of a recombinant double mutation achieved in segregants up to 68% (Velasco et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Si l'on se réfère aux voies de synthèse, cette fonction concernerait probablement l'activité MPBQ méthyl transférase (figure 3). Le gène Tph2 contrôlerait le niveau d'α-et de γtocophérols, c'est-à-dire l'activité VTE3, tandis que Thp1 contrôlerait la méthylation du MBPQ, donc la balance entre les deux branches de la synthèse (VTE4) (Demurin et al, 2004). Ces deux locus seraient indépendants (Vera- Ruiz et al, 2006), car ils sont localisés dans des groupes de liaison différents.…”
Section: Variation De Profilunclassified